Biogeochemical drivers of microbial community convergence across actively retreating glaciers. (October 2016) - Castle, Sarah C.; Nemergut, Diana R.; Grandy, A. Stuart; Leff, Jonathan W.; Graham, Emily B.; Hood, Eran; Schmidt, Steven K.; Wickings, Kyle; Cleveland, Cory C.
Abstract: The ecological processes that influence biogeographical patterns of microorganisms are actively debated. To investigate how such patterns emerge during ecosystem succession, we examined the biogeochemical drivers of bacterial community assembly in soils over two environmentally distinct, recently deglaciated chronosequences separated by a distance of more than 1300 km. Our results show that despite different geographic, climatic, and soil chemical and physical characteristics at the two sites, soil bacterial community structure and decomposer function converged during plant succession. In a comparative analysis, we found that microbial communities in early succession soils were compositionally distinct from a diverse group of mature forest soils, but that the differences between successional soils and mature soils decreased from early to late stages of succession. Overall differences in bacterial community composition between sites were explained by soil pH. However, within-site successional patterns – leading to community convergence across sites at the latest stage of succession – were explained by alternate factors such as soil organic carbon and soil organic matter chemistry, which were correlated to bacterial community structure across both glacial and mature forest soils. Highlights: We evaluated soil microbial community assembly along two recently deglaciated chronosequences. Different glacial sites harbored compositionally and functionally unique communities. Successional patterns were observed for bacterial community composition and decomposer function. Between-site community similarity increased through successional time. Within-site convergence related to soil organic matter content and chemistry.